2002
DOI: 10.1046/j.1468-1331.2002.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Machado–Joseph disease presenting as REM sleep behaviour disorder and prominent psychiatric symptoms

Abstract: A male patient carrying the homozygous gene for Machado-Joseph disease (MJD) presented at age 43 with sleep disturbances and psychiatric symptoms followed by ataxic speech and gait. A polysomnogram (PSG) showed decreased rates of sleep time and stage rapid eye movement (REM) and an increased rate of 'stage 1-REM with tonic EMG' (Tachibana et al., 1975); all compatible with REM sleep behaviour disorder (RBD). Molecular gene analysis at age 59 showed that the CAG repeat units in the MJD gene were 60 and 60, smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 17 publications
(23 reference statements)
0
22
0
1
Order By: Relevance
“…Rare alleles of intermediate repeat length fall between the clearly normal and mutant ranges and are not associated with classical clinical features of disease (Gu et al , 2004; Maciel et al , 2001; Padiath et al , 2005; Paulson, 2007; Takiyama et al , 1997; van Alfen et al , 2001; van Schaik et al , 1997). Cases of homozygosity are extremely rare in MJD; the few described homozygous patients appear to show a more severe form of disease suggesting a gene dosage effect (Carvalho et al , 2008; Fukutake et al , 2002; Lang et al , 1994; Lerer et al , 1996; Sobue et al , 1996; Takiyama et al , 1995). …”
Section: The Disease Gene Atxn3mentioning
confidence: 99%
“…Rare alleles of intermediate repeat length fall between the clearly normal and mutant ranges and are not associated with classical clinical features of disease (Gu et al , 2004; Maciel et al , 2001; Padiath et al , 2005; Paulson, 2007; Takiyama et al , 1997; van Alfen et al , 2001; van Schaik et al , 1997). Cases of homozygosity are extremely rare in MJD; the few described homozygous patients appear to show a more severe form of disease suggesting a gene dosage effect (Carvalho et al , 2008; Fukutake et al , 2002; Lang et al , 1994; Lerer et al , 1996; Sobue et al , 1996; Takiyama et al , 1995). …”
Section: The Disease Gene Atxn3mentioning
confidence: 99%
“…Diverse etiologies include cases of tauopathy related parkinsonian syndromes (Progressive supranuclear palsy, Guadaloupean parkinsonism) [149][150][151], TDP43opathies (frontotemporal dementia, amyotrophic lateral sclerosis) [7,152], amyloidopathies (Alzheimer's disease) [7,153]. RBD has also been associated with some trinucleatide repeat disorders including spinal cerebellar ataxia type 3 (SCA3) [154][155][156][157] and Huntington's disease [158]. However, with the notable exception of SCA3, none of these conditions have prevalence rates similar to synuclein disorders.…”
Section: Non-synuclein Neurodegenerative Etiologiesmentioning
confidence: 99%
“…Several clinical investigations showed that dementia in SCA3 might be less frequent (5–13%) than in other SCAs [10, 18, 31]. However, it has been reported that SCA3 patients do have various cognitive and psychiatric disorders, such as REM sleep behavior disorder [32] and delirium [33]. Maruff et al [34] examined cognitive function in 6 patients with genetically confirmed SCA3 using a series of subtests from the Cambridge Neuropsychological Test Automated Battery.…”
Section: Spinocerebellar Ataxia Type 3 (Machado-joseph Disease)mentioning
confidence: 99%